Jogos sérios como ferramentas para desenvolver soft skills no ambiente de transformação digital - Guimarães, Ana Beatriz Cobra (2025)
Digital transformation has required professionals to acquire new competencies, leading many organizations to invest in training programs aimed at skill development. However, several studies suggest that these investments do not always generate the expected returns, both financially and in terms of human resource development. In this context, serious games emerge as an innovative tool with pedagogical objectives beyond entertainment, showing promise for the development of soft skills, which are essential interpersonal competencies for professional performance. This study aimed to investigate how serious games can be used to develop these skills in the context of digital transformation, focusing on their application among managers. The research was conducted through a systematic literature review, which informed the creation of qualitative interviews with 18 professionals from various fields. The analysis of the collected data revealed that serious games are effective in enhancing soft skills and have significant potential to positively impact performance and collaboration within organizations. The results suggest that this tool can be a strategic solution to address gaps in interpersonal skill development, representing an innovative approach to the challenges posed by the digital age.